Peripheral blood flow regulation in persons with multiple sclerosis - Ketelhut, Nathaniel B., author; Fling, Brett W., advisor; Hickey, Matthew S., committee member; Chicco, Adam J., committee member; Myers, Brent, committee member (Colorado State University. Libraries, 2021)
Multiple sclerosis (MS) is an inflammatory, degenerative disease of the central nervous system that is believed to be autoimmune in nature. The disease affects approximately one million people in the United States and results in a wide variety of symptoms including impaired physical function, reduced exercise capacity, and increased fatigability. Although considerable effort has been invested in improving our understanding of the neuromuscular contributions to these symptoms, no studies have investigated whether cardiovascular autonomic dysfunction compromises skeletal muscle blood flow in persons with MS (PwMS). Indeed, approximately 50% of PwMS have an abnormal response to tests of cardiovascular autonomic function, and skeletal muscle blood flow is positively associated with exercise capacity. Thus, the overall goal of this dissertation was to determine whether PwMS have impaired skeletal muscle blood flow responses to exercise relative to age- and sex-matched healthy controls. The primary findings are that 1) the local control of skeletal muscle blood flow during exercise is intact in PwMS, 2) skeletal muscle blood flow is likely reduced during exercise that engages the autonomic nervous system in MS, which may be due to increased α-adrenergic mediated vascular tone, and 3) that PwMS may experience hypersensitivity to α-adrenergic signaling as evidenced by levels of systemic vascular resistance relative to plasma concentrations of norepinephrine. Together, these studies indicate that compromised skeletal muscle blood flow during exercise may contribute to reduced exercise capacity and increased fatigability in PwMS.
Keywords: cardiovascular; fatigue; neurological disorders; exercise capacity; blood flow; multiple sclerosis